DIAGNOSTIC AND INDICATION OF BLOOD TRANSFUSION IN APLASTIC ANEMIA - M Rizqa Fauzi (E-Jurnal Medika Udayana, 2013)
Aplastic anemia is a disease caused by a failure of the bone marrow to produce blood cells components resulting anemia with pancytopenia. symptoms will arise according to the blood cells decreased. Aplastic anemia is a rare and severe disease. The International Aplastic anemia and agranulocytosis Study found the incidence of aplastic anemia in Europe about 2 than 1,000,000 per year. Incidents in Asia 2 to 3 times higher than in Europe. In China, the incidence is estimated to 7 cases per 1,000,000 people and in Thailand is estimated to 4 cases per 1,000,000 people. The highest frequency at 15 and 25 years, the second highest peak at age 65 and 69 years. The cause of aplastic anemia majority (50-70%) is unknown. Enforcement of diagnosis based on history, physical examination, laboratory investigations and radiological either. One treatment in aplastic anemia is a blood transfusion. Blood transfusion in aplastic anemia is necessary when haemoglobin levels <7 g / dl and platelet count <20.000/?L.